They abeyant nursery - Lum, Quinn Fu Loong (2018)
Research question - How Visual Arts can be used to resolve problems related to childhood trauma caused by authoritarian parenting? Purpose - This research intends to investigate the idea of how I can use visual expression as a form of therapy to my confront fears and insecurities that inhibit me from being a balanced and whole individual. Research Limitations – This research would mainly be based on the personal case study of the author and complete objectivity would not be attainable. However, I would attempt to record his entire thought process and emotions throughout the research as form of study to be reviewed objectively in retrospect. Value of Research – This analytical research contributes a case study to show how victims of authoritarian parenting can use art making as a self help tool to better understand self identity and chronic psychological problems they face in this 21st century Singapore society.